Strategy of core curriculum to improving student’s critical thinking skill - Caraka Putra Bhakti; Muhammad Alfarizqi Nizamuddin Ghiffari; Swiejti Maghfira Regita (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2018)
The purpose of this research is the development of core curriculum that is able toincrease critical thinking skills for students. 21st Century demands that humans go on to establish themselves with various skills. There are a variety of human skills required in the 21st Century Skills Critical thinking skills to be one of the human skills needed to survive in the 21st century Critical thinking will support people in dealing with various issues it faces today through a systematic process of thinking. Core curriculum in guidance and counseling in schools will be able to improve critical thinking skills. This study is a review of the literature. From this study indicated a technique related to core curriculum that can improve critical thinking skills in students. Techniques in basic services which can be applied as blended learning, the inquiry learning, case-based learning, problem base learning and so forth.